Creep-induced structural changes in Ni-Si-B amorphous alloy - Jurikova, A.; Miskuf, J.; Csach, K.; Ocelik, V. (Проблемы прочности, 2008)
The influence of the stress annealing on the reversible structural relaxation of a Ni-Si-B amorphous ribbon was studied. Creep-induced structural changes in the amorphous structure were derived from anisothermal DSC and dilatometric experiments. It is demonstrated that considerable enthalpy and specimen length variations associated with the reversible structural relaxation are observed after previous creep at higher temperatures.